A Morphometric Examination of The Orbita Structure in Schizophrenia Patients: A Retrospective Study - Keser, Sinem; Yildiz, Sevler; Emre, Elif (My University, 2025)
Aim: To compare the orbita anthropometric measurement values of individuals diagnosed with schizophrenia with those of a healthy control group. Material and Method: The study included 156 participants as 75 schizophrenia patients and 81 healthy control subjects, all with previous cranial computed tomography imaging. The orbita morphometric values were calculated of all the participants. Statistical comparisons were made between the groups of the mean values of the measurements. The Kolmogorov-Smirnov test was used to evaluate the conformity of continuous variables to normal distribution. Paired groups were compared with the Student’s t-test. Results: Statistically significantly higher left orbita height was determined in the schizophrenia patient group compared to the control group (p=0.001), and the values of the right orbita lateral wall length (p=0.042), left lateral wall length (p=0.033), and left medial wall length (p=0.014) were statisically significantly lower. Female schizophrenia patients were found to have significantly lower values of right orbita height (p=0.031), right orbita width (p=0.022), left orbita height (p=0.007), left orbita width (p=0.002), right orbita area (p<0.001), left orbita area (p=0.023), bimalar width (p<0.001), left optic nerve-sheath width (p=0.021), and skull transverse diameter (p<0.001) compared to males. There was determined to be a significant positive correlation between age and the right orbita width and the interorbital width measurements (p=0.011, r=0.203; p=0.015, r=0.194, respectively).
Keywords: Schizophrenia; morphometry; multislice computed tomography; orbita